The Role of Islamic Religious Coping and Social Support in Parenting Stress among Working Mothers with Young Children - Zahira Naufal Putri Muslih, Qurota'aini; Nashori, Fuad (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2024)
Working mothers with multiple roles often struggle to manage internal pressures, leading to stress, including parental stress associated with the demands of raising children. Islamic religious coping and social support are factors that can influence the level of parenting stress. This study aimed to examine the relationship between Islamic religious coping, social support, and parenting stress in working mothers with young children. A quantitative approach was used in this research, targeting a population of working mothers with early childhood-aged children across Indonesia. The sample was selected through purposive sampling, with criteria: mothers who work or earn independently, have young children, and reside in Indonesia. A total of 206 respondents were included in the research sample. Validity testing was conducted using corrected item-total correlation, while reliability testing was performed with Cronbach's Alpha. The instruments used were the Parenting Stress Scale (r=0.828), the Islamic Religious Coping Scale (r=0.658), and the Social Support Scale (r=0.850). The writer analyzed the data by using multiple linear regression analysis with a stepwise regression method and a partial correlation analysis. The assumption tests included assessments of normality, linearity, multicollinearity, and heteroscedasticity. Hypothesis testing was carried out, and the effective contribution of each predictor variable was analyzed. This research is expected to contribute to parenting practices with young children.